Cover Picture: A Photoaffinity Displacement Assay and Probes to Study the Cyclin‐Dependent Kinase Family (Angew. Chem. Int. Ed. 48/2019). Issue 48 (8th November 2019) - Grant, Emma K.; Fallon, David J.; Eberl, H. Christian; Fantom, Ken G. M.; Zappacosta, Francesca; Messenger, Cassie; Tomkinson, Nicholas C. O.; Bush, Jacob T.
Abstract : Photoaffinity probes were designed to target cyclin‐dependent kinases (CDKs), which can be regarded as the timekeepers of cellular processes. As reported by J. T. Bush and co‐workers in their Research Article on page 17322 ff., these probes competitively enrich CDKs from cell lysates, and a biochemical photoaffinity displacement assay was developed to measure compound potency. The seesaw represents the balance of competition between the photoaffinity probe and competitor compound.